Start-Up Investment with Scarce Venture Capital Support - Vesa Kanniainen; Christian Keuschnigg (Center for Economic Studies and ifo Institute (CESifo), 2001)
Start-up entrepreneurs are often commercially inexperienced. In giving managerial advice, venture capitalists can importantly enhance the success of innovative but highly risky ventures. The supply of experienced venture capitalists is not easily increased, however. When the rate of business formation accelerates, the incumbent venture capitalists tend to include more firms in their portfolio which dilutes the quality of advice, making project risks excessively high in the short-run. The supply of advisory capacity eventually becomes more elastic as new venture capitalists are attracted to the industry. Company portfolios then tend to become more focused again, the quality of advice is restored and the risk of business failure declines.
Keywords: 330; Venture capital; company portfolio; managerial advice; economic rents